Viability of Streptomyces fradiae VNIIG-25’ Spore Culture after Some Factor Effect of Freeze-Drying Process - Tsutsayeva, A. A.; Ananyiina, A. E.; Pavlenko, N. V. (Problems of Cryobiology and Cryomedicine, 2004)
There was studied the effect of residual humidity indices and rehydration ways on the viability and antibiotic activity after freeze-drying of Streptomyces fradiae VNIIG-25’ spore culture. It was demonstrated, that in order to obtain the highly active samples of frozen-dried microbial culture the optimal indices of a residual humidity corresponded to 1.0-2.0% and the rehydration was carried-out by one-step addition of distilled water with following exposure for 1 hr under 20°C.